2017
DOI: 10.1016/j.vetpar.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of poultry red mite ( Dermanyssus gallinae ) native and recombinant prototype vaccines

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…Two indirect ELISA tests were performed based on previously described protocols [36] to detect IgY antibodies against both antigens in serum samples from vaccinated and control hens. One was performed to evaluate the trend on the antibody level during the whole experiment and another to compare the level of antibodies and the mite oviposition at the moment of experimental infestation.…”
Section: Analysis Of Hen Igy Antibody Response By Elisamentioning
confidence: 99%
“…Two indirect ELISA tests were performed based on previously described protocols [36] to detect IgY antibodies against both antigens in serum samples from vaccinated and control hens. One was performed to evaluate the trend on the antibody level during the whole experiment and another to compare the level of antibodies and the mite oviposition at the moment of experimental infestation.…”
Section: Analysis Of Hen Igy Antibody Response By Elisamentioning
confidence: 99%
“…Experimental vaccination with protein extracts from D. gallinae mites Wright et al, 2009;Bartley et al, 2015;Makert et al, 2016), or with recombinant-expressed D. gallinae antigens (Bartley et al, 2009(Bartley et al, , 2012(Bartley et al, , 2015Wright et al, 2016), induces antigen-specific serum IgY that reduces mite survival when fed to mites in in vitro feeding devices. Furthermore, we recently showed that vaccination of laying hens, housed in a commercial-style poultry facility, with a native PRM soluble protein extract results in protective immunity, reducing average mite counts in cages of vaccinated birds by 78% compared to cages of control, unvaccinated birds (Bartley et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we used a prototype vaccine antigen D. gallinae cathepsin D1 (Dg-CatD-1) (Bartley et al, 2012), and compared antigen delivery to laying hens by: (i) immunization with purified recombinant Dg-CatD-1 in adjuvant; (ii) recombinant DNA vaccination for expression of Dg-CatD-1 and (iii) oral challenge with populations of the live transgenic coccidial parasite Eimeria tenella expressing Dg-CatD-1. These delivery platforms were chosen to compare antigenspecific antibody titres in laying hens using tried and tested protein-in-adjuvant vaccination (Bartley et al, 2017), with new vaccine technologies which include DNA vaccination (Gupta et al, 2016;Meunier et al, 2016) and a novel experimental E. tenella antigen delivery system (Clark et al, 2012;Marugan-Hernandez et al, 2016;Pastor-Fernandez et al, 2018), in order to identify the optimal system. We assessed each delivery platform for the ability to induce specific anti-Dg-CatD-1 IgY in laying hens and monitor longevity of the response over a commercially relevant period.…”
Section: Introductionmentioning
confidence: 99%
“…Some candidate antigens have been proposed and tested based on their similarity to promising vaccine antigens from other arthropod species (Harrington et al, 2009;Wright et al, 2016). Others have been identified by painstaking "fractionate and vaccinate" approaches that use empirical logic to separate out and test the vaccine efficacy of partially purified protein mixtures extracted directly from mites (Bartley et al, 2015;Makert et al, 2016;Bartley et al, 2017).…”
Section: What About Vaccines?mentioning
confidence: 99%